The Effect of Consumer Price Index And The Amount Of Money Circulation On Net Assets Value Of Sharia Mutual Funds - Yayang Kirana Dewi; Fanji Farman; Lisna Lisnawati (LPPM Universitas Sebelas April, 2019)
This study entitled